Characterization of APOBEC3 variation in a population of HIV-1 infected individuals in northern South Africa - Matume, Nontokozo D.; Tebit, Denis M.; Gray, Laurie R.; Turner, Stephen D.; Rekosh, David; Bessong, Pascal O.; Hammarskjöld, Marie-Louise (BMC medical genetics, 2019)
Background The apolipoprotein B mRNA-editing enzyme, catalytic polypeptide-like 3 (APOBEC3) genes A3D, A3F, A3G and A3H have all been implicated in the restriction of human immunodeficiency virus type 1 (HIV-1) replication. Polymorphisms in these genes are likely to impact viral replication and fitness, contributing to viral diversity. Currently, only a few studies indicate that polymorphisms in the A3 genes may be correlated with infection risk and disease progression. Methods To characterize polymorphisms in the coding regions of these APOBEC3 genes in an HIV-1 infected population from the Limpopo Province of South Africa, APOBEC3 gene fragments were amplified from genomic DNA of 192 HIV-1 infected subjects and sequenced on an Illumina MiSeq platform. SNPs were confirmed and compared to SNPs in other populations reported in the 1000 Genome Phase III and HapMap databases, as well as in the ExAC exome database. Hardy-Weinberg Equilibrium was calculated and haplotypes were inferred using the LDlink 3.0 web tool. Linkage Disequilibrium (LD) for these SNPS were calculated in the total 1000 genome and AFR populations using the same tool. Results Known variants compared to the GRCh37 consensus genome sequence were detected at relatively high frequencies (> 5%) in all of the APOBEC3 genes. A3H showed the most variation, with several of the variants present in both alleles in almost all of the patients. Several minor allele variants (< 5%) were also detected in A3D, A3F and A3G. In addition, novel R6K, L221R and T238I variants in A3D and I117I in A3F were observed. Four, five, four, and three haplotypes were identified for A3D, A3F, A3G, and A3H respectively. Conclusions The study showed significant polymorphisms in the APOBEC3D, 3F, 3G and 3H genes in our South African HIV1-infected cohort. In the case of all of these genes, the polymorphisms were generally present at higher frequencies than reported in other 1000 genome populations and in the ExAC exome consortium database .